Radioresistance in rhabdomyosarcomas: Much more than a question of dose - Camero, Simona; Cassandri, Matteo; Pomella, Silvia; Milazzo, Luisa; Vulcano, Francesca; Porrazzo, Antonella; Barillari, Giovanni; Marchese, Cinzia; Codenotti, Silvia; Tomaciello, Miriam; Rota, Rossella; Fanzani, Alessandro; et al. (Frontiers in Oncology, 2022)
Management of rhabdomyosarcoma(RMS), the most common soft tissue sarcoma in children, frequently accounting the genitourinary tract is complex and requires a multimodal therapy. Particularly. as a consequence of the advancement in dose conformity technology, radiation therapy (RT) has now become the standard therapeutic option for patients with RMS. In the clinical practice, dose and timing of RT are adjusted based on patients’ risk stratification in order to reduce late toxicity and side effects on normal tissues. However, despite the substantial improvement in cure rates, local failure and recurrence frequently occur. In this review, we summarize the general principles of the treatment of RMS, focusing on RT, and the main molecular pathways and specific proteins involved into radioresistance in RMS tumors. Specifically, we focused on DNA damage/repair, reactive oxygen species (ROS), cancer stem cells (CSCs), and epigenetic modifications that have been reported in the context of RMS neoplasia both in vitro than in vivo studies. The precise elucidation of the radioresistance-related molecular mechanisms is of pivotal importance to set up new more effective and tolerable combined therapeutic approaches that can radiosensitize cancer cells to finally ameliorate the overall survival of patients with RMS, especially for the most aggressive subtypes.